Does running performance relate to the market value of elite male soccer players? A case study from the FIFA world cup - Kilci, A.; Koç, M. E.; Binokay, H.; Erdogan, A.; Kamis, O.; Oliveira, R. (BMC Sports Science, Medicine and Rehabilitation, 2025)
The study main aim was to investigate: the relationship between running performances and market values of soccer players playing in the 2022 FIFA World Cup, by playing position and all players; the comparisons by playing position; to analyse the relationship between running metrics and market values of the highest and lowest players ranked players. The relationship between running metrics and market values of 306 soccer players who participated in the tournament and played full time, as well as the 40 players with the highest (n = 20) and lowest (n = 20) market values was analysed. Overall, there was a very weak correlation between market values and total distance (r = 0.149), zone 3 (r = 0.153), zone 4 (r = 0.139), zone 5 (r = 0.160), high-speed runs (r = 0.132), sprints (r = 0.147), and top speed (r = 0.194) for all players (p < 0.05). Defenders showed very weak positive correlation between market values and top speed (r = 0.155, p < 0.05). Midfielders showed weak positive correlations between market values and zone 4 (r = 0.302, p < 0.05) and zone 5 (r = 0.369, p < 0.001), sprints (r = 0.367, p < 0.001), and top speed (r = 0.304, p < 0.05). Forwards showed no correlations (p > 0.05). While there is no significant correlation between running metrics and market value for players with the lowest market value (p > 0.05), there was a moderate negative correlation between total distance (r=-0.577) and zone 2 (r=-0.612) for the 20 players with the highest market value (p < 0.05). Moreover, there was a weak correlation with zone 5 (r = 0.450) and a moderate correlation with the top speed values (r = 0.596) (p < 0.05). Weak correlations between soccer players` running performance and market values suggest that different running thresholds are important metrics, although other factors (e.g., technical skill, age, national and team club) may influence this relationship. In conclusion, since coaches and scouts aim to recruit relatively talented players within the limits of their budgets, selecting athletes with high aerobic and anaerobic performance, particularly those with a strong high-intensity running profile, can contribute to team success and potentially generate high transfer revenues in the future.